Advancements in monkeypox vaccines development: a critical review of emerging technologies - Garcia-Atutxa, Igor; Mondragon-Teran, Paul; Huerta-Saquero, Alejandro; Villanueva-Flores, Francisca (Frontiers in Immunology, 2024)
Monkeypox (mpox) is a zoonotic illness caused by the monkeypox virus (MPXV), with higher health concerns among people who are pregnant, children, and persons who are immunocompromised, including people with untreated and advanced HIV disease. Significant progress has been made in developing vaccines against mpox, yet critical challenges and limitations persist in ensuring their effectiveness, safety, and accessibility. The pertinence of this review is highlighted by the World Health Organization's declaration of a global health emergency on August 14, 2024, due to the recent mpox outbreak, underscoring the critical necessity for effective vaccine solutions in the face of a rapidly evolving virus. Here, we comprehensively analyze various vaccine platforms utilized in mpox prevention, including attenuated and non-replicating virus vaccines, viral vector-based vaccines, recombinant protein vaccines, and DNA and mRNA vaccines. We evaluate the advantages and limitations of each platform, highlighting the urgent need for ongoing research and innovation to enhance vaccine efficacy and safety. Recent advancements, such as incorporating immunostimulatory sequences, improved delivery systems, and developing polyvalent vaccines, are explored for their potential to offer broader protection against diverse orthopoxvirus strains. This work underscores the need to optimize currently available vaccines and investigate novel vaccination strategies to address future public health emergencies effectively. By focusing on these advanced methodologies, we aim to contribute to the development of robust and adaptable vaccine solutions for mpox and other related viral threats.